Розпади Далiца нейтральних мезонів у Пуанкаре-інваріантній кварковій моделі - Haurysh, V. Yu.; Andreev, V. V. (Publishing house "Academperiodika", 2019)
The procedure for obtaining the radiative decay constants of pseudoscalar and vector unflavored mesons in the point-form of PiQM is presented. Based on the obtained earlier parameters of the model for light (u, d, s) quarks, we obtain the remaining parameters from the experiments on the V → Py and P → Vy decays. As a result, the mixing angles for pseudoscalar and vector mesons and the behavior of the V → Pℓ+ℓ− decay constant are obtained in agreement with modern experimental data.